AXILLARY LYMPH NODE CLIP PLACEMENT AND RESECTION AT SURGERY: A SINGLE-CENTER STUDY - Carvalho, Graziela Couto de; Rengel, Heloisa Helena Gonçalves; Monteiro, Barbara Barbosa; Venezian, Larissa Scarabucci; Mello, Aline Campos Oliveira; Rodrigues, Fábio Francisco Oliveira (Mastology, 2026)
Objective: This study aims to identify the characteristics of patients who underwent axillary lymph node clipping (ALC) and determine the detection rate with sentinel node biopsy (SNB). Methods: This is a retrospective study with a review of medical records, including patients who were submitted to ALC from 2018 to 2021 and who underwent neoadjuvant chemotherapy (CH) or upfront surgery. In patients with SNB, the clipped node was marked with Technetium-99m before surgery. Results: We identified 13 patients who underwent ALC at diagnosis: 8 were submitted to SNB and 5 to axillary dissection without SNB (4 due to poor response to CH, 1 due to lobular histology with upfront surgery). The mean age was 54 years (38% <50 years). The clinical staging was: 12 with cT2cN1 — IIB and 1 with cT3cN2 — IIIA. Concerning tumor characteristics, 12 (92%) patients had ductal histology and 1 lobular; 3 patients had triple-negative disease (23%), 8 patients had luminal disease (61%), and 2 patients had triple-positive disease (15%). In 4 of the 8 patients who underwent SNB, the clip was identified in the image after surgery (2) or in the frozen section (2), and in 4 patients, no information regarding the localization of the clip was obtained in the records regarding the surgery. However, in the follow-up images, the axillary clip was not identified, presuming that it was removed. Considering the patients who did SNB, the detection rate was 50%. Conclusion: According to previous studies, ALC at the time of diagnosis is a useful tool to guide targeted axillary dissection, reducing the false-negative rate (FNR) of SNB after CH. It is important that the clip removal check is performed. Our results reflect that this verification is not always performed, which may have reduced identification rates. However, this study encourages further prospective studies to be carried out, with standardization of techniques for clip identification, improving detection rates, and reducing FNR of SNB in these patients.